نشأة مدرسة الكوفة السنية وأسباب انتشارها: The Emergence and Development of the Sunnī Kūfah Ḥadīth School - Ali Bakhit Soleh H Mashan; Khairil Husaini Bin Jamil (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
نشأت مدرسة الكوفة السنية إثر بقاء الصحابي الجليل عبد الله بن مسعود معلماً لمدة طويلة في الكوفة، وكان لطريقته في الاستنباط الأثر العظيم عليها. وقد أثير حول هذه المدرسة وطريقتها في التعامل مع النصوص جدلاً عريضاً. وهذا المقال مقصده دراسة هذه الاتهامات ومناقشتها وبيان أن منهج هذه المدرس لا يختلف عن المدارس الأخرى إلا أن هناك من الظروف البيئية ما أدى إلى الاختلاف في التعامل مع النصوص اختلافاً ليس جذرياً. ويبين هذا المقال أسباب الاختلاف ويبين أشهر رجال هذه المدرسة. الكلمات المفتاحية: مدرسة الكوفة؛ الحديث؛ التاريخ الإسلامي؛ الرواة؛ المذاهب. Abstract The Sunnī Kūfan school emerged in pursuant of the teachings of ʿAbd Allāh ibn Masʿūd, the companion of the Prophet who resided there for a long period of time. His methodology has left a huge impact on the practices and views of this school of thought. Many issues have been raised concerning this school and its methodology. This study aims at exploring these issues and examining their contexts. It explains the reasons behind the emergence of those issues. The study will also trace the most prominent figures of this school. Keywords: Kūfah; hadith; Islamic history; narrators; madhhab.